Emerging Technologies and Generic Assays for the Detection of Anti-Drug Antibodies - Michael A. Partridge; Shobha Purushothama; Chinnasamy Elango; Yanmei Lu (Journal of Immunology Research)
Anti-drug antibodies induced by biologic therapeutics often impact drug pharmacokinetics, pharmacodynamics response, clinical efficacy, and patient safety. It is critical to assess the immunogenicity risk of potential biotherapeutics in producing neutralizing and nonneutralizing anti-drug antibodies, especially in clinical phases of drug development. Different assay methodologies have been used to detect all anti-drug antibodies, including ELISA, radioimmunoassay, surface plasmon resonance, and electrochemiluminescence-based technologies. The most commonly used method is a bridging assay, performed in an ELISA or on the Meso Scale Discovery platform. In this report, we aim to review the emerging new assay technologies that can complement or address challenges associated with the bridging assay format in screening and confirmation of ADAs. We also summarize generic anti-drug antibody assays that do not require drug-specific reagents for nonclinical studies. These generic assays significantly reduce assay development efforts and, therefore, shorten the assay readiness timeline.